The Mechanism of Aureusidin in Suppressing Inflammatory Response in Acute Liver Injury by Regulating MD2 - Yang, Yi; Han, Chenyang; Sheng, Yongjia; Wang, Jin; Zhou, Xiaohong; Li, Wenyan; Guo, Li; Ruan, Shuiliang (Frontiers in Pharmacology, 2021)
Objective In this study, we mainly explored the mechanism and target of the anti-inflammatory effects of Aureusidin (Aur) in acute liver injury. Methods Lipopolysaccharide (LPS) was used to induce inflammatory injury in Kupffer cells (KCs) in vitro. After Aur treatment with gradient concentration, flow cytometry, propidium iodide (PI) staining, and Hoechst 33342 staining were used to detect the apoptotic level of KCs, and an enzyme-linked immunosorbent assay (ELISA) was used to detect the expression levels of inflammatory factors, including Interleukin-1β (IL-1β), Interleukin-18 (IL-18), and tumor necrosis factor alpha (TNF-α). Western blot was used to detect the expression of toll-like receptor 4 (TLR4), myeloid differentiation protein-2 (MD2), MyD88, and p-P65. Aur was labeled with biotin, followed by a pull-down assay to detect its binding with MD2. Moreover, D-GalN/LPS was used to induce acute liver injury in mice in vitro, followed by Aur treatment by gavage. H&E staining was used to detect the pathological changes of liver tissue, an IF assay was used to detect the expression of MD2, Western blot was used to detect the expression of relevant proteins. Results Aur pretreatment could significantly inhibit LPS-induced KC injury, downregulate the apoptotic level, inhibit the expression of inflammatory factors, decrease the level of MDA, and downregulate the expression of MD2 in cells. Aur could inhibit the activation level of TLR4/MD2-NF-κB in a dose-dependent pattern, a high dose of Aur had a superior effect compared to low-dose Aur. In the case of MD2 deletion, the effects of Aur were suppressed. Additionally, pull-down and co-immunoprecipitation assays show that Aur can bind with the MD2 protein to inhibit the activation of TLR4/MD2-NF-κB. Results of mice experiments also showed that Aur could relieve liver injury, decrease the levels of ALT and AST, and simultaneously downregulate the levels of inflammatory factors in tissues and peripheral blood. Conclusion We found that Aur exerted an anti-inflammatory effect by directly targeting the MD2 protein, further inhibiting the expression of TLR4/MD2-NF-κB, thereby relieving acute liver injury. Therefore, Aur might be a potential inhibitor for MD2.